Warren Technique for The Correction of Portal Hypertension in Pediatric Patients - Anguila, Jorge Julian Mendoza; Alvaran, Conrado de Jesús Orozco; Miranda, Andrés Enrique Jaraba; Rojas, Maria Fernanda Riaño; Pérez, Ana María Garcés; Navarro, Ana María Pineda; Gómez, Frank David Almenares; Villada, Nataly Zuluaga (Jour Med Resh and Health Sci, 2022)
the portal vein formed by the union of the superior mesenteric vein with the blood flow from the small intestine and the pancreas, the splenic and in most cases the inferior mesenteric and gastric veins, the portal vein is responsible for draining the splanchnic flow to the liver which is used for the processing and metabolism of products derived from intestinal absorption; portal venous pressure is slightly higher than the pressure of the inferior vena cava and ranges between 0-11mmHg, when there is obstruction or resistance to venous flow in the splanchnic bed and the right atrium due to the compromise of the vascular lumen, this alteration produces an increase in the pressure of the portal vein, which leads to portal hypertension (PHT) which is defined as an increase in hydrostatic pressure in the portal system. The surgical procedure to treat this pathology consists of diverting the high pressure from the portal venous system to the systemic circulation (portosystemic shunt) or ideally to the portal circulation (mesenteric portal shunt of Rex or porto-portal shunt to the right portal vein). Portosystemic shunts are divided into porto-caval shunts and selective shunts such as Warren's distal splenorenal shunt and proximal splenorenal shunt. This procedure has given satisfactory results if you want to selectively decompress gastroesophageal varices while preserving portal perfusion of the liver, as well as the results that this procedure will be chosen over the years for its reliability and low mortality rate. and morbidity.